The Optimum Planting Time and Cropping Pattern of Potatoes and Other Horticultural Commodities based on Water Balance in Solok, Indonesia - Via Yulianti; Impron; Aris Pramudia (Agromet, 2023)
Many mountainous regions in Indonesia have been utilized for potato cultivation. But location for the cultivation is mainly a rainfed agriculture, which greatly depend on the weather condition. Lembah Gumanti in Solok, West Sumatra is a rainfed main potato-growing area, which faced a low productivity during dry season. Therefore, efforts to optimize potato production in rainfed area remains research challenge. This study aims toidentify the optimum cropping calendar for potato and other horticultural commodities in Lembah Gumanti for 2018-2021. We used the water balance approach to derive daily water availability at field level. The approach was used to identify the planting time and pattern of potato and other horticultural commodities for 2018-2023 at dekadal (10-day) interval. The results showed that the most suitable planting time and cropping patternvaried annually. In 2018-2019, the cropping calendar was potato (in October 1st 10-day) – shallots (in April 1st 10-day) – chilies (in July 3rd 10-day). For 2020-2021, the best cropping calendar was shallots (in November 3rd 10-day) – potato (in March 3rd 10-day) – shallots (in August 1st 10-day). The findings reveal that water availability determined the cropping calendar of each commodity.